1998
DOI: 10.1055/s-2007-1010247
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Leukocyte Subsets in Coronary Artery Bypass Surgery: Cardiopulmonary Bypass Versus ‘Off-pump’ techniques

Abstract: The results indicate a reaction of the leukocyte subsets to coronary bypass surgery which is more related to the surgical trauma in general than to CPB in particular.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 8 publications
5
29
0
1
Order By: Relevance
“…In agreement with earlier findings, the systemic inflammatory reactions to CPB resemble to sepsis with increased pro-and anti-inflammatory cytokine release and reduction of the activity of the cellular innate and adaptive immune system (1,(32)(33)(34). To reduce the proinflammatory reaction the majority of surgical corrections for congenital heart disease are performed under highdose GC administration (15).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In agreement with earlier findings, the systemic inflammatory reactions to CPB resemble to sepsis with increased pro-and anti-inflammatory cytokine release and reduction of the activity of the cellular innate and adaptive immune system (1,(32)(33)(34). To reduce the proinflammatory reaction the majority of surgical corrections for congenital heart disease are performed under highdose GC administration (15).…”
Section: Discussionsupporting
confidence: 85%
“…Typically, after surgical trauma T-cell numbers drop dramatically as a result of increased migration into the periphery, particularly into the lymphatic organs (34). Unfortunately, no studies exist on effects of GCs on T-lymphocytes in vivo during CPB surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the increase of C5a is accompanied by a decrease of monocytes, which was clearly demonstrated by our previously reported results. 11 This phenomenon is explained by an increased adhesion of monocytes to the endothelial surface influenced by C5a. 12 Burrows et al 13 showed an increased release of premature monocytes from the bone marrow as a secondary reaction to the acute-phase response.…”
Section: Discussionmentioning
confidence: 99%
“…It is claimed that an extensive and sometimes overwhelming systemic inflammatory response (SIRS) followed by profound immune depression leading to severe infectious complications are due to CPB (22). Based on results of some studies, it is suggested that the beating heart surgery is superior to "on pump" surgery (5,6). However, data which are gathered in this field are contradictory.…”
Section: Introductionmentioning
confidence: 99%